THE DETERMINANTS OF FINANCIAL INFORMATION TRANSPARENCY IN REGIONAL PUBLIC HOSPITAL IN INDONESIA - Sri Ningsih; Fitria Andriyani; Suham Cahyono (Universitas Gunadarma, 2023)
This research aims to examine the influence of hospital size, hospital type, hospital management, and Bed Occupancy Rate (BOR) on the financial transparency of Regional Public Hospitals in Indonesia. The sample size used in this study was 162 Regional Public Hospitals, selected through purposive sampling. The data collected for this research was secondary data. The study employed a quantitative approach, utilizing data analysis, descriptive statistical analysis, and logistic regression analysis as the method for hypothesis testing. The results of this research indicate that hospital size and hospital management have a positive influence on the financial transparency of Regional Public Hospitals. However, the type of hospital and Bed Occupancy Rate (BOR) do not affect the financial transparency of Regional Public Hospitals. This study offers a novelty in examining the openness of public hospital information transparency through four measurements, whereas previous studies only focused on three measurements. The contribution of this research lies in presenting an expansion of the literature on public sector accounting, particularly regarding the transparency of hospital information, using four main measurements.